2022
DOI: 10.1007/s00266-022-03214-w
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery After Aesthetic Breast Surgery Under Sedation, Intercostal Block and Tumescent Anaesthesia: A Prospective Cohort Study of the Early Postoperative Phase

Abstract: Background Comfort and recovery are major concerns of patients seeking aesthetic surgery. This study aimed to assess postoperative pain and recovery after outpatient breast surgery under sedation, intercostal block, and local anaesthesia. Methods This prospective cohort study included all consecutive patients who underwent aesthetic breast surgery between April 2021 and August 2022. Epidemiological data, anaesthesia, pain, and patients’ satisfaction were systematically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…The higher doses of propofol and alfentanil typically administered in general anesthesia difficult recovery, especially in the first 48 h, and therefore are more likely to require inpatient hospitalization postoperatively. The authors have previously shown that patients after aesthetic breast surgery according to the ERAS protocol described herein are recovering sooner than expected after general surgery (drinking, eating, and voiding within a median (IQR) of 0:45 (1:19–0:25) h, discharge within a median of 2:40 (3:43–1:58) h [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The higher doses of propofol and alfentanil typically administered in general anesthesia difficult recovery, especially in the first 48 h, and therefore are more likely to require inpatient hospitalization postoperatively. The authors have previously shown that patients after aesthetic breast surgery according to the ERAS protocol described herein are recovering sooner than expected after general surgery (drinking, eating, and voiding within a median (IQR) of 0:45 (1:19–0:25) h, discharge within a median of 2:40 (3:43–1:58) h [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pain, nausea, and drowsiness are the most frequent causes for delaying discharge [ 30 ]. Evidence has been presented that opioid-sparing anesthesia improves recovery without compromising patient safety and pain control [ 13 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations